(untitled) (Nigerian Journal of Technology, 2021)
Power outages and blackouts have continued to characterize household electricity supply despite the desire of Nigerians to have improved quality of electricity supply. Nigeria has an installed electric power capacity of 12,500MW but power sent out daily as at the end of June 2019 was 3,419MW. This is 200kWh per capita, which is a fraction of 4,229kWh per capita for South Africa. Worst still, Nigerians have only 59.3% access to electricity and those connected to the grid face extensive power interruptions. Attainment of stable and reliable electricity supply requires three basic dimensions: technicalities, organisational structures and reduction of Electricity Theft (ET) to the barest minimum. Previous studies have focussed more on the technical and organisational requirements than on issues bothering on ET and its resultant effects on stable electricity supply. Therefore, this study investigated the prevalence of ET among households in Lagos State, Nigeria. A self-constructed structured questionnaire focusing on demographic characteristics and prevalence of ET was purposively administered to 580 households (area of franchise under Ikeja Electric Plc. = 330, under Eko Electricity Distribution Company = 250), using the statistical sample size determination formula. Descriptive and inferential statistics was used to identify and analyse prevalence of ET among households. The extensive Electricity theft among households in Lagos State, Nigeria, was exacerbated by weak enforcement of anti-electricity theft laws with severe consequences on the entire electric power value chain. Strengthening institutions for enforcement and application of anti-electricity theft laws is recommended to mitigate the problem.